Cushing's syndrome in a case of thymic carcinoma - Asha, H. S. (Medknow Publications, 2011)
A 29-year-old gentleman presented with episodic features suggestive of Cushing's syndrome. He was evaluated and diagnosed with ectopic Adrenocorticotropic hormone (ACTH)–dependent Cushing's syndrome due to a thymic tumor. The thymic lesion was excised and histopathology confirmed thymic carcinoma with neuroendocrine differentiation, with local, perineural, and vascular invasion. The postoperative problems and further treatment options have been discussed in this case report.